2015
DOI: 10.17770/etr2015vol2.280
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of two perch Perca fluviatilis populations of the Latgale region

Abstract: Molecular markers based on retrotransposons possibility of integration into genomes of many organisms are commonly used for genetic analysis of different species. The aim of this study was to test possibility of use those markers in perch and detect genetic diversity of populations of two lakes of the Latgale region of Latvia: Cirišs and Sventes. The distance between the lakes is nearly 60 km, they belong to the same Daugava river basin but are different from ecological point of view. Forty two blood samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These are typical periodic migrations for grazing and spawning. Migrations of perch from Pomeranian Bay to the Szczecin Lagoon are also confirmed by analyses conducted by Garbacik-Wesołowska and Boberski (2000). Perch inhabiting the coastal zone of the Baltic Sea probably pass the longest distances among the known perch stocks-their range is up to 80 km (Król 2008).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These are typical periodic migrations for grazing and spawning. Migrations of perch from Pomeranian Bay to the Szczecin Lagoon are also confirmed by analyses conducted by Garbacik-Wesołowska and Boberski (2000). Perch inhabiting the coastal zone of the Baltic Sea probably pass the longest distances among the known perch stocks-their range is up to 80 km (Król 2008).…”
Section: Discussionmentioning
confidence: 77%
“…They can be defined as forms with a highly arched back in reservoirs rich in food, and elongated forms with a poorly arched back in reservoirs poor in food. A study by Fokina et al (2015) revealed a possibility of genetic diversity of two perch populations whose geographical area of occurrence was limited to the catchment area of one river in Latvia. The distance between the two lakes from which the fish were sampled was approx.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted on the consequences of overexploitation and subsequent population recovery of Eurasian perch (Perca fluviatilis L.) populations (Pukka et al, 2016), and the impacts of a nuclear power plant on the genetic structure of perch populations as an intensively exploited fish species (Ragauskas et al, 2014). It was shown that genetic differences are not related to geo-graphical distances, but probably depend on ecological characteristics (Fokina et al, 2015). Eurasian perch was used for investigations on the relative importance of genetic variation and plasticity on phenotypic variation (Svanbäck and Eklöv, 2006).…”
Section: Introductionmentioning
confidence: 99%